Pengembangan Multimedia Tutorial Berfitur Peta Konsep Untuk Belajar Lapisan Bumi Siswa MTS - Moh. Dwi Handoko; Sulthoni Sulthoni; Saida Ulfa (JKTP: Jurnal Kajian Teknologi Pendidikan, 2021)
Abstract: Multimedia tutorials on earth layers become complementary in science learning and teaching at MTs Negeri 2 Nganjuk. Earth layer multimedia tutorials are designed to enhance science subject materials which take role as enrichment or remedial in conventional learning. Earth layer multimedia tutorials are learning media that can be used independently or in groups with excellent concept maps to increase students motivation as well as comprehension. The purpose of this development is to produce multimedia tutorials, as well as to discover the validity of the developed multimedia. This research model uses Lee & Owens. The results of the development of the Earth Layer Multimedia Tutorial as a complement to science learning with the concept map feature received positive responses from media and material experts and was feasible to use and there was an increase learning outcome Abstrak: Multimedia tutorial lapisan bumi menjadi pelengkap dalam  pembelajaran IPA di MTs Negeri 2 Nganjuk. Multimedia tutorial lapisan bumi didesain untuk menguatkan  materi pelajaran IPA yang bersifat enrichment atau remidial dalam pembelajaran konvensional. Multimedia tutorial lapisan bumi adalah media pembelajaran yang dapat digunakan secara mandiri maupun kelompok yang  memiliki fitur unggulan peta konsep untuk meningkatkan motivasi dan pemahaman belajar siswa. Tujuan pengembangan ini menghasilkan multimedia tutorial, serta mengetahui kelayakan dari multimedia yang dikembangkan. Model Penelitian ini menggunakan model Lee & Owens. Hasil pengembangan Multimedia Tutorial Lapisan Bumi sebagai Komplemen Pembelajaran IPA berfitur Peta Konsep mendapatkan respon positif oleh ahli media dan ahli materi serta layak digunakan dan ada peningkatan hasil belajar.